DEVELOPMENT OF THE BASICS OF FINGERING TECHNIQUE IN THE PIANO STYLE OF G.DEMESINOV'S MUSIC - Hojametova, G.I. (SCIENCE and SOCIETY, 2024)
The article reveals the style and genre of piano works by Karakalpak composer G. Demesinov, the expressive possibilities of the piano - its timbre, dynamic colors, coloristic palette. Especially, the declamation of themes plays a great role where along with the melodies of wide breathing, giving the music epic narrative, restraint and majesty.